International Business Cycle - Marek Lubiński (Contemporary Economics, 2007)
Prime stylized facts of international business cycle theory refer to positive correlation in the cyclical components of important macroeconomic variables across countries. However a number of indicators of business cycle synchronization do not point to clear trends. It can be ascribed to the fact that different forces influence level of business cycle correlation. When investigating into the forces behind the commonness in aggregate fluctuations economic research seems to have pointed in two directions. One strand of the literature examines the idea of common exogenous shocks that affect economies simultaneously. In addition to that economic interdependencies such as trade in goods and services or capital account transactions may serve as the channels through which disturbances spill over across countries.The observed degree of output co movement reflects both the nature of the shocks that have occurred and the degree of economic interdependence. In the periods when common shocks prevail level of synchronization is usually higher than in times of transmission dominance.